2018
DOI: 10.1038/s41467-018-03399-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of the social brain from age three to twelve years

Abstract: Human adults recruit distinct networks of brain regions to think about the bodies and minds of others. This study characterizes the development of these networks, and tests for relationships between neural development and behavioral changes in reasoning about others’ minds (‘theory of mind’, ToM). A large sample of children (n = 122, 3–12 years), and adults (n = 33), watched a short movie while undergoing fMRI. The movie highlights the characters’ bodily sensations (often pain) and mental states (beliefs, desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
376
4
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(420 citation statements)
references
References 73 publications
22
376
4
2
Order By: Relevance
“…Marked improvement in social cognitive skills during childhood and adolescence is generally considered to be the dominant developmental focus of this highly dynamic age range (Blakemore, 2008). The brain regions implicated in "the social brain" are some of the most densely connected in the cortex (McCormick et al, 2018;Oldham and Fornito, 2019;Saxe et al, 2009), and previous studies have shown that significant changes in FC organization of these regions occurs during development (Richardson et al, 2018). Recently, Lake et al used Connectome Predictive Modeling to identify a complex set of FC edges that predict SRS scores in a large sample of children and adolescents with and without autism spectrum disorder (Lake et al, 2019).…”
Section: Social Scores and Functional Connectivitymentioning
confidence: 99%
“…Marked improvement in social cognitive skills during childhood and adolescence is generally considered to be the dominant developmental focus of this highly dynamic age range (Blakemore, 2008). The brain regions implicated in "the social brain" are some of the most densely connected in the cortex (McCormick et al, 2018;Oldham and Fornito, 2019;Saxe et al, 2009), and previous studies have shown that significant changes in FC organization of these regions occurs during development (Richardson et al, 2018). Recently, Lake et al used Connectome Predictive Modeling to identify a complex set of FC edges that predict SRS scores in a large sample of children and adolescents with and without autism spectrum disorder (Lake et al, 2019).…”
Section: Social Scores and Functional Connectivitymentioning
confidence: 99%
“…Additionally, mentalizing-selective temporo-parietal cortex (TPJ-M) was localized using the Pixar short-film 'Partly Cloudy' (2009), by modelling responses to timepoints that reliably evoke responses to mentalizing (along with 'pain', 'social' and 'control' timepoints) as described previously (Richardson et al, 2018). However, as this region did not respond strongly to interaction stimuli, these data are not reported in the main text (see supplementary materials C for further details).…”
Section: Mri Tasks and Experimental Sessionmentioning
confidence: 99%
“…Further, our MEG data were recorded when the children were watching cartoon of their own choice. This framework of data collection is being increasingly used in neuroimaging studies with young children Richardson et al (2018), one limitation is that we cannot dis-criminate between task-driven and intrinsic contributions to the temporal variability of FCN. For example, the negative correlations between left parahippocampal region and mental processing scale might reflect a combination of both intrinsic changes in network structure and increasing stability of the cartoon-driven response in the selected region.…”
Section: Age-related Increase In Temporal Variabilitymentioning
confidence: 99%